Augmented Reality (AR) for Promoting Public Participation in Urban Planning / Ahmad Johari Awang, M. Rafee Majid and Noradila Rusli. - Awang, Ahmad Johari; Majid, M. Rafee; Rusli, Noradila (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
Public participation plays a vital role for the developer and local government as this ensures the acceptance of the general public to the proposed project. However, the general public participation rate in the planning process in Malaysia is still at a low level. Hence, this study was conducted to study the use of augmented reality (AR) as a tool in promoting public participation in the planning process. In the study that was conducted, 77 respondents were selected from the general public to evaluate the effectiveness of AR. During this evaluation process, 37 of them were given AR material, and another 40 of them were given classic plan material. By using feedbacks from the public, statistical analysis was done to study the effect of AR and conventional plan material on the willingness for public participation process. The statistical test shows that the participant is more willing to participate in the public participation process when AR material is being used.